π0 and [eta] meson production in proton-proton collisions at √s=8 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; Ohlson, Alice; Pachmayer, Yvonne C.; et al. (The European physical journal. C, Particles and fields, 2018)
An invariant differential cross section measurement of inclusive π0π0\pi ^{0} and ηη\eta meson production at mid-rapidity in pp collisions at s√=8s=8\sqrt{s}=8 TeV was carried out by the ALICE experiment at the LHC. The spectra of π0π0\pi ^{0} and ηη\eta mesons were measured in transverse momentum ranges of 0.3<p T <350.3<p T <350.3<p_{ \text{ T }} <35 GeV/c GeV/c \text{ GeV/c } and 0.5<p T <350.5<p T <350.5<p_{ \text{ T }} <35 GeV/c GeV/c \text{ GeV/c }, respectively. Next-to-leading order perturbative QCD calculations using fragmentation functions DSS14 for the π0π0\pi ^{0} and AESSS for the ηη\eta overestimate the cross sections of both neutral mesons, although such calculations agree with the measured η/π0η/π0\eta /\pi ^0 ratio within uncertainties. The results were also compared with PYTHIA 8.2 predictions for which the Monash 2013 tune yields the best agreement with the measured neutral meson spectra. The measurements confirm a universal behavior of the η/π0η/π0\eta /\pi ^0 ratio seen for NA27, PHENIX and ALICE data for pp collisions from s√=27.5s=27.5\sqrt{s}=27.5 GeV to s√=8s=8\sqrt{s}=8 TeV within experimental uncertainties. A relation between the π0π0\pi ^{0} and ηη\eta production cross sections for pp collisions at s√=8s=8\sqrt{s}=8 TeV is given by m T m T m_{ \text{ T }} scaling for p T >3.5p T >3.5p_{ \text{ T }} >3.5 GeV/c GeV/c \text{ GeV/c }. However, a deviation from this empirical scaling rule is observed for transverse momenta below p T <3.5p T <3.5p_{ \text{ T }} <3.5 GeV/c GeV/c \text{ GeV/c } in the η/π0η/π0\eta /\pi ^0 ratio with a significance of 6.2σ6.2σ6.2\sigma .
Im Titel werden "pi" und "eta" als griechische Buchstaben dargestellt
Im Titel ist 0 hochgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, M.K. Köhler, S. Klewin, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 04.07.2019